Critical pathways for the management of preeclampsia and severe preeclampsia in institutionalised health care settings - Daftari Ashi; Reinharz Daniel; Reyes Hortensia; Fraser William; Perez-Cuevas Ricardo; Heinz Cristina S; Roberts James M (BMC, 2003)
Abstract Background Preeclampsia is a complex disease in which several providers should interact continuously and in a coordinated manner to provide proper health care. However, standardizing criteria to treat patients with preeclampsia is problematical and severe flaws have been observed in the management of the disease. This paper describes a set of critical pathways (CPs) designed to provide uniform criteria for clinical decision-making at different levels of care of pregnant patients with preeclampsia or severe preeclampsia. Methods Clinicians and researchers from different countries participated in the construction of the CPs. The CPs were developed using the following steps: a) Definition of the conceptual framework; b) Identification of potential users: primary care physicians and maternal and child health nurses in ambulatory settings; ob/gyn and intensive care physicians in secondary and tertiary care levels. c) Structural development. Results The CPs address the following care processes: 1. Screening for preeclampsia, risk assessment and classification according to the level of risk. 2. Management of preeclampsia at primary care clinics. 3. Evaluation and management of preeclampsia at secondary and tertiary care hospitals: 4. Criteria for clinical decision-making between conservative management and expedited delivery of patients with severe preeclampsia. Conclusion Since preeclampsia continues to be one of the primary causes of maternal deaths and morbidity worldwide, the expected impact of these CPs is the contribution to improving health care quality in both developed and developing countries. The CPs are designed to be applied in a complex health care system, where different physicians and health providers at different levels of care should interact continuously and in a coordinated manner to provide care to all preeclamptic women. Although the CPs were developed using evidence-based criteria, they could require careful evaluation and remodelling according to each system's demands. Additionally, the CPs need to be tested in large-scale, multi-level studies in order to thoroughly examine and evaluate their efficacy and effectiveness.